2018
DOI: 10.1007/s12088-018-0738-9
|View full text |Cite
|
Sign up to set email alerts
|

New Insights on Cyclization Specificity of Fungal Type III Polyketide Synthase, PKSIIINc in Neurospora crassa

Abstract: Type III polyketide synthases (PKSs) biosynthesize varied classes of metabolites with diverse bio-functionalities. Inherent promiscuous substrate specificity, multiple elongations of reaction intermediates and several modes of ring-closure, confer the proteins with the ability to generate unique scaffolds from limited substrate pools. Structural studies have identified crucial amino acid residues that dictate type III PKS functioning, though cyclization specific residues need further investigation. PKSIII, a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
(70 reference statements)
0
6
0
Order By: Relevance
“…Type III PKSs are more rarely described in fungi. At present, ten of these PKSs have been reported from Ascomycota and only one from Basidiomycota, and they play several physiological roles in such processes as pigmentation, salinity and dehydration resistance, stress adaptation, and cell wall remodeling ( Parvez et al, 2018 ; Navarro-Muñoz and Collemare, 2019 ). To the best of our knowledge, no reports have described this kind of secondary metabolite cluster in C. sake and Cryptococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Type III PKSs are more rarely described in fungi. At present, ten of these PKSs have been reported from Ascomycota and only one from Basidiomycota, and they play several physiological roles in such processes as pigmentation, salinity and dehydration resistance, stress adaptation, and cell wall remodeling ( Parvez et al, 2018 ; Navarro-Muñoz and Collemare, 2019 ). To the best of our knowledge, no reports have described this kind of secondary metabolite cluster in C. sake and Cryptococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…The equivalent position in PKSIII of N. crassa (position 120) is a key residue in determining enzymatic function. It has been shown that substitution of a C120 by a phenylalanine or serine in PKSIIINc results in synthesis of phloroglucinol instead of α-pyrone [50]. The active site is flanked by the acyl-binding tunnel similar to those observed in the structures of bacterial and fungal PKSIII [38,39,47,50,53].…”
Section: Residues Of Active Sitementioning
confidence: 79%
“…The modelling revealed that this protein could form a dimer complex, like other fungal PKSIII ( Figure 2 A). We compare PKSIII Mo29 amino acids involved in substrate binding with those found in PKSIII from PKSIII from N. crassa (PKSIIINc) [ 37 , 47 , 50 ], Mycobacterium tuberculosis (PKS18) [ 51 ], two PKSIII from Aspergillus oryzae (AoCsyA and AoCsyB) [ 38 , 39 , 52 ], PKSIII from Botrytis cinerea (BcPKS) [ 53 ] and PKSIII from Aspergillus niger (AnPKS) [ 41 ]. The active site residues cysteine 171, histidine 351 and asparagine 385 (catalytic sites) are conserved ( Table 1 and Figure 2 B) ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations